(untitled) (Journal of Statistics on Health Decision, 2022)
Objective To evaluate the etiology and types of oral and maxillofacial injuries in Portugal. Materials and Methods An epidemiological clinical observational study was performed in Centro Hospitalar Lisboa Norte with a sample of 384 subjects diagnosed with oral and maxillofacial trauma, between 2018 and 2020. Data was collected through clinical reports and analyzed in SPSS, version 27. Results Both sexes had a similar distribution, 49.5% females and 50.5% males. 2020 had a lower amount of trauma compared to the remaining years. Falls were the most frequent etiology (44.3%), followed by assault (24.7%). The upper central incisors (174) were the most affected teeth with uncomplicated fractures and the most frequent treatment was the prescription of painkillers. Conclusion A relationship between falls, women, and age increase, and between assault, men and adults have been highlighted. Falls and assault were the main etiology and 2020 shows a decline in the number of traumas due to the current pandemic situation.